Politics of memorialization in Angola: Erasing and controlling contested pasts - Blanes, R. L. (The Palgrave encyclopedia of cultural heritage and conflict, 2025)
This contribution maps the specific dynamics of the politics of heritagization and memorialization of conflict in Angola, arguing for the idea of a logic of “militarization of memory” in process. Focusing on heritage landmarks such as the São Miguel Fort, the Casa de Reclusão Militar, the São Nicolau camp, as well as on the topography and toponymy of Luanda, it argues that, more than responding to a conception of heritage as a tool toward the promotion of peace and reconciliation, the politics of memorialization in Angola reflects strategies of political domination and control associated to partisan contingencies. As a result, it portrays a heritage landscape populated at the same time by mobilized, domesticated, controlled, and silenced pasts.